Pembelajaran Inovatif Abad Ke-21 - Muhali, Muhali (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2019)
[Title: The 21st Century Innovative Learning]. The 21st-century education paradigm has experienced a shift marked by differences in learning orientations. The learning of the previous century emphasized literacy in reading, writing, and mathematics, wherein the 21st century they were used as the basis for developing new literacy, namely human, data and technological literacy which is very important to face the current and future globalization era. Innovative learning in the 21st century is oriented towards activities to practice essential skills according to the framework for 21st-century skills, namely life and career skills, innovation and learning skills, and information, media and ICT skills. Learning characteristics to train these essential skills, lead to learning processes that are interactive, holistic, integrative, scientific, contextual, thematic, effective, collaborative, and student-centred so that in their implementation educators can design activities by selecting learning methods/models that can accommodate overall characteristics are comprehensive. Assessment in 21st century learning is compiled and developed to measure student learning achievement which includes knowledge competencies (critical thinking and problem solving, creativity and innovation, collaboration, communication), intrapersonal competencies (work skills in teams, collaboration, communication, cooperation, and coordination), and interpersonal competence (the ability to work with others such as the ability to self-management, cooperation, effective communication, and the ability to maintain relationships with others emotionally). Thus, innovative learning in the 21st century creates human resources that are literate with information, data and technology that are needed to face the competition for life and the labour market in the current and future globalization era.